2021
DOI: 10.24042/terampil.v8i1.9200
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesulitan Siswa Kelas V Sekolah Dasar dalam Menyelesaikan Soal Cerita pada Materi Bangun Ruang

Abstract: Kedekatan matematika dengan kehidupan sehari-hari menjadikan matematika sebagai salah satu ilmu yang sangat penting untuk dipelajari. Dalam lingkup pendidikan formal, matematika dijadikan sebagai mata pelajaran yang selalu hadir di setiap jenjang termasuk pada jenjang pendidikan Sekolah Dasar. Salah satu bahasan matematika yang menjadi kajian pada jenjang pendidikan Sekolah Dasar adalah bangun ruang yang dapat disajikan dengan tujuan memberikan pengalaman bagi siswa untuk dapat memecahkan masalah matematika da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
0
0
2
Order By: Relevance
“…These problems aligned with a study by Putri & Pujiastuti (2021) in Serang Regency, showing that students had difficulty learning solid geometry, especially understanding nets (cubes and cuboids), and had difficulty answering volume questions about cubes and cuboids), thus requiring learning media that can increase student learning interest. Similar problems have also become a concern in previous research by Chuseri et al (2021) revealed when working on solid geometry questions, students' scores below the passing grade (KKM) had a mean of 53.71, with the percentage of students below the KKM of 81.25% because students had difficulty in working on HOTS (Higher-order thinking skills) type questions.…”
Section: Introductionsupporting
confidence: 79%
“…These problems aligned with a study by Putri & Pujiastuti (2021) in Serang Regency, showing that students had difficulty learning solid geometry, especially understanding nets (cubes and cuboids), and had difficulty answering volume questions about cubes and cuboids), thus requiring learning media that can increase student learning interest. Similar problems have also become a concern in previous research by Chuseri et al (2021) revealed when working on solid geometry questions, students' scores below the passing grade (KKM) had a mean of 53.71, with the percentage of students below the KKM of 81.25% because students had difficulty in working on HOTS (Higher-order thinking skills) type questions.…”
Section: Introductionsupporting
confidence: 79%
“…Namun, ada ruang untuk peningkatan dalam penulisan rumus dan identifikasi informasi awal. Seperti yang diungkapkan oleh Putri & Pujiastuti (2021) bahwa kemampuan literasi memiliki peran signifikan.…”
Section: Soal Nomorunclassified
“…Penelitian sebelumnya juga telah mengungkapkan adanya kesulitan siswa sekolah dasar dalam menyelesaikan soal cerita (Al Husna et al, 2021;Mandasari & Rosalina, 2021;Syah Putri & Pujiastuti, 2019;Utari et al, 2019). Padahal soal cerita memiliki peranan penting, salah satunya dapat melatih siswa untuk menyelesaikan suatu permasalahan sesuai alur atau kerangka kerja yang telah direncanakan (Abidin, 2011).…”
Section: Pendahuluanunclassified